Theories and models of IT efficiency in public administration - Pokataiev, Pavlo; Arutiunian, Volodymyr (Management and Entrepreneurship: Trends of Development, 2024)
The article focuses on the analysis of modern theoretical approaches and practical models of information technology use in the field of public administration. The purpose of the article is to study and analyze various theories and practical models used to improve the efficiency of information technology implementation in public administration. Special attention is paid to investigating how IT can optimize work processes, increase transparency, and provide more effective citizen services. The article also aims to identify the most effective strategies and methods for implementing IT solutions in the public administration sector, taking into account the specifics and needs of the Ukrainian context. The research methodology includes several key components, among which is the deep analysis of scientific literature focusing on existing theories and models of IT in public administration, allowing for a systematic review of research in this field. The methodology involves using comparative analysis to evaluate the effectiveness of different IT models in public administration in various countries. It includes studying specific examples of IT initiative implementations in public administration. Applying qualitative analytical tools for information assessment and conclusions. This methodology allows for a thorough and comprehensive investigation of how IT can enhance efficiency in public administration and identify best practices and strategies for their implementation. Results: The development of e-governance and the use of IT in public administration in Ukraine and worldwide shows significant progress in increasing the accessibility and quality of public services, as well as in strengthening democratic processes. However, to achieve the maximum potential of digitalization, it is necessary to ensure continuous improvement of the technological base, strengthen cybersecurity, develop digital literacy, and actively involve all stakeholders in the process of implementing and using IT innovations in public administration.JEL Classification: H 70, H 73